An efficient audio message transmission using QR-code - Sheshang Degadwala, Dr; Arpana Mahajan, Mrs.; Dhairya Vyas, Mr (International Journal of Engineering and Technology, 2018)
Introduction: Temporomandibular joint (TMJ) dysfunction (TMJD) is a group of related disorders of the muscles of mastication. Until now, no research has been conducted with particular attention to intra oral lateral pterygoid release along with conventional therapy.Methods: The study was performed an experimental study and the samples were recruited in convenient sampling method. 30 patients were selected and divided them into two groups, Group A & B. The measurement of range of maximal mouth opening (MMO) and pain using the NPRS and TMD disability index was observed.Results: All the outcome measures were analysed at baseline and after 4 weeks of treatment using appropriate statistical test. Level of significance was kept at 95%. Both the groups A and B, p values were <0.001, showing statistically signifacant difference in MMO, NPRS and TMDI score as compared to baseline.Conclusion: The lateral pterygoid release technique along with ultrasound and conventional therapy is more effective in reducing pain, increasing range of mouth opening and reducing functional disability of TMJD than conventional therapy and ultrasound alone.Â Â